(untitled) (University Journal of Zoology, Rajshahi University, 2012)
An experiment was conducted for a period of eight weeks under laboratory conditions to determine the effect of different salinity levels on the survival and growth of crablings of mud crab, Scylla serrata. The different salinity levels tested were: 5 ppt, 10 ppt, 15 ppt, 20 ppt and 25 ppt. The differences in growth increment in terms of body weight (BW) were significant (p<0.05) among different salinity treatments. The specific growth rate (SGR%/day) values of 2.67, 2.85, 4.07, 4.39 and 4.46 at 5 ppt, 10 ppt, 15 ppt, 20 ppt and 25 ppt, respectively were found significant (p<0.05). The survival rates of crablings were found to be the highest (47.67%) at 25 ppt and lowest (10%) at 5 ppt (p<0.05). The results indicated that increase of salinity from 5 to 25 ppt had significant effect on the survival and growth of mud crablings. Key words: Mud crabling; salinity; specific growth rate; survival rate DOI: http://dx.doi.org/10.3329/ujzru.v29i1.9462 UJZRU 2010; 29(1): 29-32